2018
DOI: 10.1136/bmj.k2400
|View full text |Cite
|
Sign up to set email alerts
|

Risk of meticillin resistant Staphylococcus aureus and Clostridium difficile in patients with a documented penicillin allergy: population based matched cohort study

Abstract: ObjectiveTo evaluate the relation between penicillin allergy and development of meticillin resistant Staphylococcus aureus (MRSA) and C difficile.DesignPopulation based matched cohort study.SettingUnited Kingdom general practice (1995-2015).Participants301 399 adults without previous MRSA or C difficile enrolled in the Health Improvement Network database: 64 141 had a penicillin allergy and 237 258 comparators matched on age, sex, and study entry time.Main outcome measuresThe primary outcome was risk of incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
188
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(197 citation statements)
references
References 42 publications
5
188
0
4
Order By: Relevance
“…• 2014-2018-Impact of penicillin labels on Clostridioides difficile 32,33 • 2016-Recognition of the need to address penicillin allergy by Centers for Disease Control, Infectious Disease Society of America antimicrobial stewardship guidelines 34…”
Section: Acqu Is Iti On Of Peni Cillin Allergy L Ab El Smentioning
confidence: 99%
“…• 2014-2018-Impact of penicillin labels on Clostridioides difficile 32,33 • 2016-Recognition of the need to address penicillin allergy by Centers for Disease Control, Infectious Disease Society of America antimicrobial stewardship guidelines 34…”
Section: Acqu Is Iti On Of Peni Cillin Allergy L Ab El Smentioning
confidence: 99%
“…The effect of choosing different antibiotic classes for perioperative prophylaxis to impact CDI rate is largely unknown, and changing to a lower risk agent could induce undesired risk of a different adverse effect (e.g., nephrotoxicity) . Failing to address penicillin allergies appropriately led to increased non–β‐lactam antibiotics and increased CDI incidence in a recent population‐based matched cohort study . Therefore, antimicrobial stewardship goals to prevent CDI should focus on using the shortest effective duration, fewest number of agents, and antibiotic allergy clarification …”
Section: Restricted and Preferred Antimicrobialsmentioning
confidence: 99%
“…43 Failing to address penicillin allergies appropriately led to increased non-blactam antibiotics and increased CDI incidence in a recent population-based matched cohort study. 44 Therefore, antimicrobial stewardship goals to prevent CDI should focus on using the shortest effective duration, fewest number of agents, and antibiotic allergy clarification. 8…”
Section: Antimicrobial Stewardship Programsmentioning
confidence: 99%
“…The National Institute for Health and Care Excellence said that around 10% of people are documented as having an allergy to penicillin but that only 5% of these have a genuine allergy 12. The advice follows a paper in The BMJ which found that people who were treated as though they had a penicillin allergy were almost 70% more likely to develop MRSA and 25% more likely to develop C difficile because they were treated with broad spectrum antibiotics.…”
Section: Drug Resistancementioning
confidence: 99%